Effect of coffee husk and cocoa pods biochar on phosphorus fixation and release processes in acid soils from West Cameroon. (6th March 2023) - Pouangam Ngalani, Gilles; Ondo, Jean Aubin; Njimou, Jacques Romain; Nanseu Njiki, Charles Peguy; Prudent, Pascale; Ngameni, Emmanuel
Abstract: Acid soil in West Cameroon has limited phosphorus (P) availability which limits plant growth. This is mainly because of low pH, high levels of exchangeable aluminium (Al) and iron (Fe) and fixation of P. In this study, acid soils, sampled in Bafang, were amended with biochar produced from coffee husks (CH) and cocoa pod husks (CP) at two different temperatures (350 and 550 °C) in other to evaluate the effect on the physicochemical properties of the acid soil and the effect on P sorption and desorption. The soil was amended with biochar at a rate of 0, 20, 40 and 80 g/kg and incubated for 7 and 60 days. Physicochemical properties of all soil–biochar samples were determined followed by sorption experiments and data fitted in the Langmuir and Freundlich isotherm models in other to evaluate soil P sorption capacity and its affinity to soil amended with biochar. Moreover, desorption studies were done to evaluate the availability of P in soil amended with biochar after sorption. The outcomes of this study reveal an increase in soil pH, electrical conductivity (EC), available P, soil organic carbon and a drastic decrease in exchangeable Al and Fe. The point of zero charge of biochar‐amended soil was higher than the control and increased with amendment rate. The experimental data of the sorption of P on soils and soil–biochar samples fits into Langmuir and Freundlich models ( R 2 > 0.9) suggesting that the P adsorption is controlled by both model mechanisms. Soil–biochar mixture results in a decrease in the sorption capacity as compared with the control and the decrease was predominant with increasing amendment rate. At amendment rates of 20, 40 and 80 g/kg after 7 days of incubation, Q max for SCH350 were 2267, 2048 and 1823 mg/kg which increased to 2407, 2112 and 1990 mg/kg after 60 days of incubation. This tendency was observed for all biochar inputs with respect to the increase in incubation days. Furthermore, desorption of P from soil–biochar mixtures was enhanced with biochar added at greater rate and produced at higher temperature. The desorption percentage was increased by more than around 10% for all biochar types from 20 mg/kg to 80 mg/kg amendment. Thus, biochar addition to acid soils reduces P fixation to acid soil and improves P desorption to soil solution, thereby providing more available P in the soil solution and better conditions for plant growth.